A novel optical diffuser based on polymer micro-balls-filled nematic liquid crystal composite film. Issue 70 (4th December 2018) - Zhou, Le; Han, Cheng; Zhang, Cuihong; Zhang, Lanying
Abstract : A novel optical diffuser (transmission >94%, haze >94%) with the A6 polymer morphology has excellent light diffusing ability. Abstract : In this study, optical diffusers based on epoxy resin/thiol/nematic liquid crystal composites were prepared using different curing temperatures, curing times and curing agents (thiols). Additionally, the effects of the curing temperatures, the curing times and the thiols on the polymer ball microstructures and the optical properties of optical diffusers were investigated systematically. For applications of optical diffusers, the optimized curing temperature has been achieved by combining the high transmittance and high haze. A novel optical diffuser with ultrahigh transmittance (>94.0%), ultrahigh haze (>94.0%) and excellent diffusing ability has been obtained, of which the polymer morphology is single polymer micro-balls without aggregation.